Genome-Wide Identification, Evolution, and Expression Patterns of the Fructose-1,6-Bisphosphatase Gene Family in Saccharum Species - Chunyan Tian; Xiuting Hua; Peifang Zhao; Chunjia Li; Xujuan Li; Hongbo Liu; Xinlong Liu (Plants)
Fructose-1,6-bisphosphatase (FBP) is a crucial regulatory enzyme in sucrose synthesis and photosynthetic carbon assimilation, functioning through two distinct isoforms: cytosolic FBP (cyFBP) and chloroplastic FBP (cpFBP). However, the identification and functional characterization of FBP genes in Saccharum remains limited. In this study, we conducted a systematic identification and comparative genomics analyses of FBPs in three Saccharum species. We further examined their expression patterns across leaf developmental zones, spatiotemporal profiles, and responses to diurnal rhythms and hormonal treatments. Our analysis identified 95 FBP genes, including 44 cyFBPs and 51 cpFBPs. Comparative analyses revealed significant divergence in physicochemical properties, gene structures, and motif compositions between the two isoforms. Expression profiling indicated that both cyFBPs and cpFBPs were predominantly expressed in leaves, particularly in maturing and mature zones. During diurnal cycles, their expression peaked around the night–day transition, with cpFBPs exhibiting earlier peaks than cyFBPs. FBP genes in Saccharum spontaneum displayed greater diurnal sensitivity than those in Saccharum officinarum. Hormonal treatments further revealed significant regulatory divergence in FBP genes, both between isoforms and across species. Notably, cyFBP_2 and cpFBP_2 members consistently exhibited higher expression levels across all datasets, suggesting their pivotal roles in sugarcane physiology. These findings not only identify potential target genes for enhancing sucrose accumulation, but also highlight the breeding value of S. spontaneum and S. officinarum in sugarcane breeding.